Peningkatan Motivasi, Kedisiplinan dan Keahlian Siswa-Siswi Yayasan Al-Mutakabbir Kabupaten Bogor - Saragih, Muhammad Rizal; Rusdi, Rusdi; Hunein, Hamida; Sadewa, Prima; Nurullah, Mawardi; Hasan, Julian Muhammad; Septiningrum, Liana Dwi; Prasetya, Eka Rima; Yudawirawan, Moh. Yuddy; Arini, Dewi Ulfah; Sujarwo, Sujarwo; Margie, Lyandra Aisyah; Habibah, Habibah; Afriadi, Fiqih; Febriyanto, Fery Citra (Jurnal PKM Manajemen Bisnis, 2025)
The objective of this community service initiative is to enhance the motivation, discipline, and expertise of students at the Al-Mutakabbir Foundation in Bogor Regency. This program employs seminars and discussions as its primary methods of engagement. The target population for this activity consists of 50 students from the foundation. During the community service event, participants were exposed to a series of interactive seminars designed to address key topics relevant to their personal and academic development. Experts and facilitators led discussions that encouraged students to actively engage with the material, share their perspectives, and collaborate on solutions to common challenges they face. One significant outcome of this initiative was the heightened motivation observed among students. Many expressed renewed enthusiasm for their studies and a clearer understanding of their personal goals. Additionally, the emphasis on discipline helped students recognize the importance of time management and consistent effort in achieving success. The participants demonstrated their understanding through practical applications of the concepts discussed, such as creating personalized action plans for their studies and developing strategies for overcoming obstacles. The objectives of the service were not only met but exceeded, laying a solid foundation for the students' ongoing development.